وظائف حرف الواو في النحو العربي: The Functions of Letter Wa in Arabic Syntax - Abdul Hafidz Zaid; fairus sholeh (Insyirah: Jurnal Ilmu Bahasa Arab dan Studi Islam, 2021)
This research aims to describe the opinions of Nuhat in the letter “و” and its functions, and its characteristics in relationship with other functions with the aim of avoiding errors in Arabic syntax and the ability to differentiate all the functions of the letter “و” in Arabic sentences. This research is qualitative and library research in a descriptive method. The data in this research comes from traditional and contemporary books related to the topic. This research relied on two data analysis methods: the content analysis method and the comparison method. The results of this research were: that the “و” for Nuhat is one of the common letters of nouns and verbs, and it performs the function of a working letter, which is: Wawu al-Qasam, Wawu al-Ma’iyyah, and Wawu Rab. And the non-working letter, which are: Wawu al-Athf, Wawu al-Isti’naf, Wawu al-Hal, and Wawu al-I’tiradh. All functions have characteristics, including: 1) Wawu al-Qasam occurred at the beginning of the sentence, after which al-Ismu al-Dhahir sentence and al-Ma’rifah al-Majrur, 2) Wawu Rab occurred at the beginning of the sentence, and then an-Nakirah al-Majrur sentence, 3) Wawu al-Ma’iyyah preceded the sentence or whit “ما” or with "كيف", 4) Wawu al-‘Athf has been mentioned in Arabic sentences between al-Ma’thuf and al-Ma’thuf ‘alaihi, 5) Wawu al-Hal may enter into the nominative and the verb sentences with a condition preceded in the speech by al-Ma’rifah, after which it is a declarative sentence, 6) Wawu al-Isti’naf occurred in the beginning of the resumed sentence, 7) Wawu al-I’tiradh may have occurred in the first sentence of the objection to the place of her expression.